2019
DOI: 10.1002/admt.201800532
|View full text |Cite
|
Sign up to set email alerts
|

MZI‐Based All‐Optical Modulator Using MXene Ti3C2Tx(T = F, O, or OH) Deposited Microfiber

Abstract: As a new class of 2D materials, MXenes have attracted a lot of interest because of their prominent performance in versatile applications, such as batteries, supercapacitors, catalysts, electronics, and optics. In this work, an all‐optical modulator using MXene Ti3C2Tx deposited on a microfiber is proposed. By inserting an MXene‐deposited phase shifter into one arm of a Mach–Zehnder interferometer, the MXene Ti3C2Tx absorbs the control light and generates heat, which induces significant refractive index changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 57 publications
0
71
0
Order By: Relevance
“…[26][27][28] Various physical mechanisms have been investigated to modulate optical light fully in the photonics domain. [29][30][31][32][33][34][35][36][37][38][39][40][41] Among these, AOMs based on the photothermal effect exhibit remarkable advantages for their large modulation depth, wide operating wavelength range, and easy implementation. Graphene, [31] transition metal dichalcogenides (TMDs) [32,38] and phosphorene [39] have been successfully employed in this kind of AOM because of their large photo-thermal effect.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Various physical mechanisms have been investigated to modulate optical light fully in the photonics domain. [29][30][31][32][33][34][35][36][37][38][39][40][41] Among these, AOMs based on the photothermal effect exhibit remarkable advantages for their large modulation depth, wide operating wavelength range, and easy implementation. Graphene, [31] transition metal dichalcogenides (TMDs) [32,38] and phosphorene [39] have been successfully employed in this kind of AOM because of their large photo-thermal effect.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Previous research studies have suggested that the band gap of GQDs in the diameters of approximately 5-35 nm are less than approximately 1.0 eV. Previous theoretical study 30,31 supports such notion. Previous theoretical study 30,31 supports such notion.…”
Section: Resultsmentioning
confidence: 91%
“…Currently, two main strategies are employed for the surface modification of MNPs: ligand replacement and encapsulation . Ligand replacement requires the exchange of native hydrophobic ligands on the surface of MNPs with strong anchoring groups (such as catechols, phosphonates, sulfonates, thiols, and carboxylic acids), which simultaneously introduces hydrophilic ligands on the surface of MNPs to promote dispersion in biological media 19b,22c,37.…”
Section: Use Of Surface Ligand‐mediated Mnps For Constructing Stimulimentioning
confidence: 99%
“…Among various nanomaterials, superparamagnetic iron oxides nanoparticle (SPION)‐based magnetic nanoparticles (MNPs) have experienced increasingly wide utilization in many biomedical fields such as drug delivery, magnetic separation, diagnostic imaging, biosensors, and hyperthermia treatments . The versatility of magnetic particles depends substantially on their size, size distribution, shape, low cytotoxicity, intrinsic magnetic properties, and surface properties . Therefore, a number of MNPs have been applied in early clinical trials and have been approved by the FDA for medical imaging and therapeutic applications…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation